A importância do gênero literário poema na construção de uma comunidade leitora: o poema “morte e vida severina” como ferramenta no processo cognitivo de incentivo à cultura da leitura - COSTA, Maria Dorianna Ribeiro (2019)
This work, titled "The importance of the literary genre poem in the construction of a reading community: the poem Morte e Vida Severina as a tool in the cognitive process of encouraging the culture of reading", has as main objective to discuss about the relevance of working the reading, departing from the literary genre poem. For this, we used authors such as Barthes (1985), Lajolo (2011), Freire (1981), Vargas (2000), Pires (2000), Zilberman (1988). Additionally, a brief intervention activity was applied to a class of the 9th grade B of the Perciliano Corrêa Tourão School, on April 2, 2019, in the afternoon, in order to verify in practice the applicability of the use of the poem genre in Portuguese language classes. It is concluded that the use of such genre can add important discussions to the Portuguese language classes, related to situations that are part of the students' world knowledge, making the classes more interesting and close to the reality of the students, favoring the work with reading and producing texts.